Prevalence of Depression among Geriatric Population and its Association with Dependency: A Cross-Sectional Study in Rural Eastern Haryana, India - Swati Jarole; Himani Tak; Satish Kumar Aggarwal (Indian Association of Preventive and Social Medicine, 2024)
Introduction: Depression in the elderly is becoming common and has dangerous implications on elderly that not only lowers quality of life, but it also has an impact on the prognosis of other chronic conditions leading to disability. According to WHO, depression occurs in 7% of elderly population and in India prevalence of depression among elderly is 9.3%. Objective: To estimate the prevalence of depression among geriatric age group and to determine the association between the depression and the dependency among geriatric population. Method: Present cross sectional study was conducted with 220 villagers of age above 60 years from catchment area of Rural Health training center of medical college. The identification of depression and dependency was carried out using the Geriatric Depression Scale (GDS) and Barthel Index respectively. Results: The prevalence of depression and dependency among the geriatric population was found out to be 28 % and 31%, respectively. There was significant association between median scores of Barthel Index among depressed and non-depressed individuals (p value< 0.001). There was significant association between depression and dependency (P value=0.05). Conclusion: The present study shows 28% of prevalence of depression among elderly population and dependency as a significant risk factor for depression, thus showing the importance of analyzing dependency status while screening for the mental health status of the elderly person.